2007
DOI: 10.1177/0001699307074879
|View full text |Cite
|
Sign up to set email alerts
|

Is Friendship Consistent with Competitive Market Exchange?

Abstract: A conventional assumption within sociology of markets is that social ties are crucial in economic life, but that too strong relationships between sellers and buyers can create role conflicts and restrict business. Using qualitative interviews with Norwegian exporters and Danish importers, this article examines transactions in the international fish trade. We find that the assumed episodic and highly competitive commodity trade is rooted in dyadic networks and personal trust; inspired by the work of Goffman, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
(17 reference statements)
0
5
0
1
Order By: Relevance
“…We found that trade can be described as socially embedded across case studies, whereby relational embeddedness often relies on stable business relationships that imply reciprocal commitments. This result highlights the importance of considering the social factors that influence food trade beyond economic motivations alone (Dulsrud andGrønhaug 2007, Stoll et al 2020). However, we also found that different types of social relationships can coexist within such complex trade networks that span spatial scales, connecting small-scale producers to local and global markets.…”
Section: Trading Is Socially Embedded In All Food Systems But the Cha...mentioning
confidence: 98%
See 2 more Smart Citations
“…We found that trade can be described as socially embedded across case studies, whereby relational embeddedness often relies on stable business relationships that imply reciprocal commitments. This result highlights the importance of considering the social factors that influence food trade beyond economic motivations alone (Dulsrud andGrønhaug 2007, Stoll et al 2020). However, we also found that different types of social relationships can coexist within such complex trade networks that span spatial scales, connecting small-scale producers to local and global markets.…”
Section: Trading Is Socially Embedded In All Food Systems But the Cha...mentioning
confidence: 98%
“…This result is in line with literature highlighting the role of embeddedness for innovation, learning, or problem-solving (e.g., Uzzi 1996, Charterina et al 2016). However, the maintenance of certain embedded relationships and dense social structures, often linked to the concept of over-embeddedness (Uzzi 1996), can also be associated with negative outcomes (Fafchamps and Minten 2002, Dulsrud and Grønhaug 2007, Turgo 2016. For instance, they could promote coping strategies that enable short-term responses but could threaten the long-term capacity to deal with changes, such as credits used as a response to changes in relationships between small-scale fishers and traders (Ferse et al 2014, Drury O'Neill et al 2019.…”
Section: Trading Is Socially Embedded In All Food Systems But the Cha...mentioning
confidence: 99%
See 1 more Smart Citation
“…Processing level and product type add to the market complexity. Shelf life/product perishability is another important consideration in the global seafood business because it represents a precondition for international market choice and marketing channel decisions (for a detailed discussion around these issues, see Dulsrud and Grønhaug (2007), Ottesen and Grønhaug (2003), Tuu and Olsen (2013)).…”
Section: Data Collectionmentioning
confidence: 99%
“…The importance of the personal relations between a seller and a buyer has been further addressed by Dulsrud and Grønhaug (2007), who refer to social events as "important bricks in market-building processes." Social arrangements and familiarity can be found in episodic transactional relations.…”
Section: Casual Exchanges With Frequent Buyersmentioning
confidence: 99%